The Effect of Leverage, Firm Size, and Audit Opinion on Audit Delay in Consumer Non-Cyclical Companies Listed on the Indonesia Stock Exchange (2020–2024) - Devina Ardelia Ramdhani; Ajeng Luthfiyatul Farida (LP2M IAIN Palopo, 2026)
The timely submission of audited financial statements is a critical aspect of ensuring the relevance of financial information to stakeholders. However, some companies still experience audit delays, making it necessary to investigate the factors that influence them. This study aims to analyze the effects of leverage, firm size, and audit opinion on audit delays among companies in the non-cyclical consumer sector listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employs a quantitative approach using secondary data obtained from annual financial statements and independent auditors’ reports. The research sample consists of 44 companies with a total of 220 observations selected using purposive sampling. Data analysis was performed using multiple linear regression with IBM SPSS Statistics version 27, including descriptive statistical analysis, classical assumption tests, the coefficient of determination test, the simultaneous test (F-test), and the partial test (t-test). The results of the study indicate that, when considered individually, leverage, firm size, and audit opinion do not have a significant effect on audit delay. However, when considered simultaneously, these three variables have a significant effect on audit delay. These findings provide empirical evidence that audit delay is influenced by a combination of firm characteristics; therefore, future research should consider other variables to improve the model’s ability to explain audit delay.